Economic Development Insights into Company Value: Exploring the Effects of Company Size, Capital Structure, Liquidity, and Profitability in the Food and Beverage Sector - Yempormase, Petrosina; Hermuningsih, Sri; Maulida, Alfiatul (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to examine the influence of company size, capital structure, liquidity, and profitability on the company value of food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period. A quantitative research approach was employed, with the sample selected using a purposive sampling method based on specific criteria. The analysis was conducted using linear regression techniques with the SPSS version 23 software. The findings of the study reveal that: (1) company size has a negative and significant effect on company value, (2) capital structure has a positive but insignificant effect on company value, (3) liquidity has a positive and significant effect on company value, and (4) profitability has a negative but insignificant effect on company value.